Coping with Climate Change Principles and Asian Context - Chandrappa, Ramesha; Kulshrestha, Umesh Chandra; Gupta, Sushil; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
The Environmental and climatic issues varies from continent to continent and is unique to Asia. Understanding the issues does need lot of research and study material which students may not be able to gather due to shortage of time and resources. Hence an effort is made by authors gathering there experience and academic input from renowned universities of world. Climate change is real and coping with it is major concern in coming days. Most of the books written and sold in the past need updating and customizing. The general description of climate change and world will not help the professionals and students. It needs to seen area wise as a professional will work in specific geographic area. Hence an effort is made to collect data from Asia which host most populated countries along with ecological hot spots.
The History of Climate Change -- Industrial Revolution, Climate Change and Asia -- Changing Environment - Where will this lead to? -- Greenhouse Gas Inventory -- Climate Change & Hydro-Meteorological Risks in Asia -- Asian Geological Settings its Effect on Climate Change and Disaster -- Climate and non Climatic Hazards -- Asian Context -- Predicting Disaster Asian Scenario -- Early Warning Systems and their Effectiveness in Asia -- Disaster Risk Reduction and Climate Change Adaptation in Asia -- Prediction of regional climate change -- Capacity Assessment - is Asia ready to face Climate Change -- Hazard and Risk Assessment -- Preventing and Mitigation of Disasters -- Sea Level Change and Asia -- Impact of Biodiversity - Asian Scenario -- Changing Livelyhood due to Climate Change - Asian Perspective -- Accelerating Innovation and Decelerating Climate Change.-.
Keywords: Geography; Climate change; Earth sciences; Popular works; Quality control; Reliability; Industrial safety; Social sciences; Geography; Geography, general; Climate Change Management and Policy; Earth Sciences, general; Social Sciences, general; Quality Control, Reliability, Safety and Risk; Popular Science, general; Electronic books